Directing Drugs to Bugs: Antibiotic-Carbohydrate Conjugates Targeting Biofilm-Associated Lectins of Pseudomonas aeruginosa - Meiers, Joscha (J Med Chem, 2020)
[Image: see text] Chronic infections by Pseudomonas aeruginosa are characterized by biofilm formation, which effectively enhances resistance toward antibiotics. Biofilm-specific antibiotic delivery could locally increase drug concentration to break antimicrobial resistance and reduce the drug’s peripheral side effects. Two extracellular P. aeruginosa lectins, LecA and LecB, are essential structural components for biofilm formation and thus render a possible anchor for biofilm-targeted drug delivery. The standard-of-care drug ciprofloxacin suffers from severe systemic side effects and was therefore chosen for this approach. We synthesized several ciprofloxacin-carbohydrate conjugates and established a structure–activity relationship. Conjugation of ciprofloxacin to lectin probes enabled biofilm accumulation in vitro, reduced the antibiotic’s cytotoxicity, but also reduced its antibiotic activity against planktonic cells due to a reduced cell permeability and on target activity. This work defines the starting point for new biofilm/lectin-targeted drugs to modulate antibiotic properties and ultimately break antimicrobial resistance.